Using the Perspectives of Advanced Practice Providers to Design Strategies to Increase Engagement of Surgical Patients in Advance Care Planning - Christopher L. Johnson, MA; Katherine E. Barnes, BS; Alexis Colley, MD, MS; Jeanette Broering, PhD, MPH, RN; Alisa Yee, MSN; Tasce Bongiovanni, MD, MPP; Sanziana Roman, MD; Elizabeth C. Wick, MD (Annals of Surgery Open)
Objective:. Advanced practice providers (APPs) are essential members of surgical teams. We sought to understand the barriers and facilitators they perceive when participating in advanced care planning (ACP) discussions with patients and use this knowledge to design strategies to promote interprofessional ACP uptake for surgical services and potentially extend ACP discussions and documentation to more patients. Background:. ACP has been challenging to integrate into surgical practice despite being endorsed by national societies and payors as an essential aspect of caring for older adults. Methods:. Using qualitative and quantitative methods, we surveyed and interviewed APPs at a single tertiary academic medical center. A previously validated Likert scale survey of clinician knowledge, attitudes, and experiences with ACP was adapted to include demographic information and details about practice experience. Results:. Of the 88 APPs who were sent our surveys, 46 (52%) responded. Eighty-eight percent of respondents believed APPs play an important role in ACP discussions, 80% believed that ACP information was helpful in guiding clinical care discussions, 71% expressed comfort with discussing ACP with patients, and 59% endorsed comfort with communicating a prognosis to patients. Twelve interviews yielded 3 main themes: (1) clinical and professional benefits of ACP; (2) barriers to APP involvement in ACP; (3) proposed interventions to integrate APPs into ACP. Conclusions:. To increase surgical ACP uptake by APPs, data on proposed ACP interventions must focus on establishing a multi-disciplinary team-based workflow, addressing competing clinical demands, opportunities for additional education, and clarifying the scope of work.